2018
DOI: 10.1002/eap.1691
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate‐severity wind disturbance in mature temperate forests: legacy structure, carbon storage, and stand dynamics

Abstract: Wind is one of the most important natural disturbances influencing forest structure, ecosystem function, and successional processes worldwide. This study quantifies the stand-scale effects of intermediate-severity windstorms (i.e., blowdowns) on (1) live and dead legacy structure, (2) aboveground carbon storage, and (3) tree regeneration and associated stand dynamics at four mature, mixed hardwood-conifer forest sites in the northeastern United States. We compare wind-affected forests to adjacent reference con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 102 publications
(162 reference statements)
4
33
0
Order By: Relevance
“…However, low-severity fire does produce a pulse of shade-tolerant cohorts, following a slow and sporadic recruitment from other disturbances that do not remove as much litter and duff, which may inhibit establishment of small seeded species. In contrast, endogenous or exogenous mortality mechanisms that create canopy gaps promote advanced regeneration as opposed to seedling regeneration as they slowly diversify forest structure over time (Whitmore 1989, Franklin and Van Pelt 2004, Meigs and Keeton 2018.…”
Section: Discussionmentioning
confidence: 99%
“…However, low-severity fire does produce a pulse of shade-tolerant cohorts, following a slow and sporadic recruitment from other disturbances that do not remove as much litter and duff, which may inhibit establishment of small seeded species. In contrast, endogenous or exogenous mortality mechanisms that create canopy gaps promote advanced regeneration as opposed to seedling regeneration as they slowly diversify forest structure over time (Whitmore 1989, Franklin and Van Pelt 2004, Meigs and Keeton 2018.…”
Section: Discussionmentioning
confidence: 99%
“…In the silvicultural system, time between entries may be based on the return interval of intermediate-severity disturbances in that forest type and region. Intermediate-severity disturbances result in a wide range of stand structures and alter developmental pathways [15,92,120,121], and thus, provide wide flexibility to forest managers for incorporation into management plans.…”
Section: How May These Events Influence Our Management?mentioning
confidence: 99%
“…Intermediate-severity disturbances typically increase stand-level structural complexity through coarse woody debris inputs, creation of canopy voids, alteration of the seedbed, and changes in the light regime [14,15,73,80,121,122]. Importantly, intermediate-severity disturbances often result in multi-aged stands [123].…”
Section: How May These Events Influence Our Management?mentioning
confidence: 99%
“…The results of our study show that the impact of the tropical cyclone Lionrock led to the appearance of windthrow patches, decreasing tree stem density by 52.6% and basal area by 58.5%. Everham and Brokaw [10] reported that trees significantly damaged by strong winds die off. In this study, we found that the proportion of standing cyclone-damaged trees was 13.8%.…”
Section: Discussionmentioning
confidence: 99%